Efficacy and Safety of Generic Sofosbuvir Plus Daclatasvir and Sofosbuvir/Velpatasvir in HCV Genotype 3-Infected Patients: Real-World Outcomes From Pakistan - Mushtaq, Saima; Akhter, Tayyab Saeed; Khan, Amjad; Sohail, Aamir; Khan, Arshad; Manzoor, Sobia (Frontiers in Pharmacology, 2020)
Background Direct-acting antivirals (DAAs) therapeutic regimens are highly effective against chronic hepatitis C virus (HCV) infection. However, HCV patients with genotype 3 (GT3) respond in a suboptimal way. This study aims to identify which of the DAAs-based therapeutic regimens are the best option for GT3. Methods Multiple governments and private tertiary care hospitals were involved in this real-life study of HCV-GT3 patients treated with DAAs. The efficacy and safety of generic sofosbuvir+daclatasvir±ribavirin (SOF+DCV±RBV) and sofosbuvir/velpatasvir±ribavirin (SOF/VEL±RBV) were assessed under the National Hepatitis C Program of Pakistan. Results Out of 1,388 participants, 70% of patients received SOF+DCV in government tertiary care hospitals and 30% received SOF/VEL in private tertiary care hospitals. The overall sustained virological responses (SVR) was 95.5%. The SVR rates at 12 weeks were comparable between SOF+DCV (94.4%) and SOF/VEL (94.7%) in chronic HCV patients. However, The SVR rates at 24 weeks were high in cirrhotic patients treated with SOF/VEL+RBV (88%) then SOF+DCV+RBV (83%). Non-responders were high in SOF-DCV than SOF-VEL (4.1 vs 3.8%, P = 0.05) regimen. In multivariate models, the significant predictors of non-SVR were age >60 years (odds ratio [OR] 4.46; 95% CI, 2.35–8.46, P = <0.001) and cirrhosis (OR 53.91; 95% CI, 26.49–109.6, P = <0.001). Skin rash (51 vs 44%) and oral ulcers (45 vs 40%) were high in patients receiving SOF-DCV then SOF-VEL. Conclusions Overall, the generic SOF+DCV ±RBV and SOF/VEL ± RBV achieved equally high SVR12 rates. However, SOF/VEL+RBV achieved a high SVR rate in cirrhotic patients then SOF+DCV+RBV. Old age and cirrhosis were significant predictors of reduced odds of SVR regardless of the regimen. Furthermore, the regimens were well tolerated in chronic HCV patients.